Use of banana (Musa sp.) pseudostem hay in feedlot sheep feeding - Silveira Junior, Jose Assuncao; Pedreira, Marcio dos Santos; Del Rei, Antonio Jorge; Silva Freitas, Claudio Eduardo; Silva, Henrique Almeida da; Soares, Maxwelder Santos [UNESP]; Oliveira, Alana Alves de; Hora, Fernanda Ferreira da (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2020)
The objective with this study was to evaluate intake, feeding behavior, rumen fluid characteristics, performance, and nutrient digestibility of sheep fed banana pseudostem hay (BPH) with and without virginiamycin (VM). Thirty-two uncastrated male crossbred Dorper x Santa Ines lambs at approximately five months of age, with an average initial body weight of 25.00 +/- 1.95 kg, were used in the experiment. Four diets were tested, as follows: Tifton grass hay (TGH) plus concentrate with VM; BPH replacing 60% of TGH plus concentrate with VM; TGH plus concentrate without VM; and BPH replacing 60% of TGH plus concentrate without VM. The experiment was set up as a completely randomized design in a 2 x2 factorial arrangement, in which the factors were represented by BPH and TGH with and without VM, organized in an orthogonal contrast. Banana pseudostem hay inclusion influenced nutrient intake, except for non-fibrous carbohydrates corrected for ash and protein. Neither idling nor water intake times were changed by VM inclusion or banana pseudostem hay addition. Rumen fluid pH did not differ among the contrasts (THV+BHV) vs. (TH+BH), THV vs. TH, and BHV vs. BH, which were used to evaluate VM influence. Banana pseudostem increased rumen fluid pH in the contrast THV vs. BHV, both treatments including VM. Mean temperature of rumen fluid was 34.07 degrees C, and it did not change by inclusions of VM or banana pseudostem hay. No difference was observed for crude protein digestibility in the evaluated contrasts. When associated with virginiamycin, banana pseudostem hay provides satisfactory performance and nutritional parameters for feedlot sheep. Virginiamycin does not change the performance or nutritional parameters of these animals when Tifton grass hay is used as the only roughage source.
Keywords: digestibility; feeding additive; feed evaluation; feed intake; tannin